REVIEW on the scientific article by Yaroslav Savchenko "Digitalization of Processes in Small Service Businesses" - Pereshliuga, Kseniia (Global Prosperity, 2025)
REVIEW on the scientific article by Yaroslav Savchenko "Digitalization of Processes in Small Service Businesses"